Characterization of a protozoan Phosducin-like protein-3 (PhLP-3) reveals conserved redox activity. - Rachel L Kooistra; Robin David; Ana C Ruiz; Sean W Powers; Kyle J Haselton; Kaitlyn Kiernan; Andrew M Blagborough; Ligin Solamen; Kenneth W Olsen; Catherine Putonti; Stefan M Kanzok (PLoS ONE, 2018)
We recently identified three novel thioredoxin-like genes in the genome of the protozoan parasite Plasmodium that belong to the Phosducin-like family of proteins (PhLP). PhLPs are small cytosolic proteins hypothesized to function in G-protein signaling and protein folding. Although PhLPs are highly conserved in eukaryotes from yeast to mammals, only a few representatives have been experimentally characterized to date. In addition, while PhLPs contain a thioredoxin domain, they lack a CXXC motif, a strong indicator for redox activity, and it is unclear whether members of the PhLP family are enzymatically active. Here, we describe PbPhLP-3 as the first phosducin-like protein of a protozoan organism, Plasmodium berghei. Initial transcription analysis revealed continuous low-level expression of pbphlp-3 throughout the complex Plasmodium life cycle. Attempts to knockout pbphlp-3 in P. berghei did not yield live parasites, suggesting an essential role for the gene in Plasmodium. We cloned, expressed and purified PbPhLP-3 and determined that the recombinant protein is redox active in vitro in a thioredoxin-coupled redox assay. It also has the capacity to reduce the organic compound tert-Butyl hydroperoxide (TBHP) in vitro, albeit at low efficiency. Sequence analysis, structural modeling, and site-directed mutagenesis revealed a conserved cysteine in the thioredoxin domain to be the redox active residue. Lastly, we provide evidence that recombinant human PhLP-3 exhibits redox activity similar to that of PbPhLP-3 and suggest that redox activity may be conserved in PhLP-3 homologs of other species. Our data provide new insight into the function of PhLP-3, which is hypothesized to act as co-chaperones in the folding and regulation of cytoskeletal proteins. We discuss the potential implications of PhLP-3 as a thioredoxin-target protein and possible links between the cellular redox network and the eukaryotic protein folding machinery.